Maritime security and the law of the sea - Klein, Natalie (Natalie S.) (Oxford monographs in international law., 2011)
Maritime security is of increasing importance in a world threatened by terrorism, piracy, and drug-trafficking. This book sets out and evaluates the legal framework regulating the use of force on the oceans, as well as challenges like illegal fishing and environmental damage. It suggests that more flexible rules are needed to safeguard the seas.